Hubungan Intensitas Penggunaan Gadget dengan Perkembangan Sosial Anak Usia Prasekolah Di TK Negeri Canggai Putri Karimun - Iratul Mirad; Mira Agusthia; Rachmawaty Rachmawaty (Lembaga Pengembangan Kinerja Dosen, 2024)
Social Development means the acquisition of the ability to behave in accordance with social demands. Becoming a person capable of socializing requires three processes. Among them are learning to behave in a socially acceptable manner, playing acceptable social roles, and the development of social traits. One of the factors that influences children's social development is the continuous use of gadgets which has a negative impact on children. This research aims to analyze the relationship between the intensity of gadget use and the social development of preschool-aged children at the Canggai Putri Karimun State Kindergarten. Method: This type of research is quantitative research with a cross sectional approach, and uses a questionnaire as an instrument. The sampling technique used was total sampling with a sample size of 80 respondents. The results of this study showed that as many as (37.5%) children used gadgets with an intensity of > 75 minutes/day and (62.5%) children had disturbed social development. The results of the chi-square correlation test obtained a p-value of 0.015 (p < 0.05), which means there is a significant relationship between the intensity of gadget use and the social development of preschool age at the Canggai Putri Karimun State Kindergarten. Based on the research results, it is recommended that parents be more selective in providing toys to their children and need supervision and firmness in giving children limits when playing with gadgets.